Does inclusive leadership foster employee psychological resilience? The role of perceived insider status and supportive organizational climate - Xintian, Li; Peng, Peng (Frontiers in Psychology, 2023)
Introduction Employee psychological resilience correlates with individual performance and well-being, which can help employees cope with work pressure under a complex situation. Drawing upon social identity and information processing theories, this paper explores how inclusive leadership stimulates employees’ psychological resilience by integrating the cross-level mediation effect of perceived insider status. This study scrutinized the moderating function of supportive organizational climate with inclusive leadership and employees’ perceived insider status, which expanded the inclusive leadership influence boundary. Methods This study used a cross-sectional survey design and collected two-wave data from individuals who are currently employed in the context of Chinese organizations. Multiple linear regression was used to analyze the paired survey data of 220 employees of valid samples. Results Inclusive leadership was positively related to employee psychological resilience; Perceived insider status mediated the relationship between inclusive leadership and employee psychological resilience; The indirect relationship above is moderated by supportive organizational climate such that the positive relationship will be enhanced when the supportive organizational climate is high, rather than low. Discussion The theoretical and practical implications of these findings are discussed.